Patient Views on the USPSTF Statement Regarding the Annual Screening Pelvic Exam [23M]. (May 2018) - Shelton, Justin A.; Style, Alyssa; Horn, Philip; Goldberg, Jay
Abstract : INTRODUCTION: The screening pelvic exam has been an integral part of the gynecologic annual well-woman visit. A recent US Preventative Services Task Force (USPSTF) statement states that there is insufficient evidence to support or refute the performance of annual screening pelvic exams in asymptomatic, non-pregnant adult women. METHODS: Patients in an outpatient gynecologic resident continuity clinic were asked to complete a 14-question survey inquiring about their views on annual screening pelvic exams, as well as demographic information. Statistical analysis was performed using the Student's t -test. RESULTS: 100 female patients, ranging from 15 to 64 years of age, completed the survey. 81% identified as African American or Hispanic/Latino. 63% were insured by either Medicaid or Medicare. 94% reported an annual household income < $50, 000. 69% were unaware of the recent statement regarding annual screening pelvic exams made by the USPSTF. 66% believed that the annual screening pelvic exam was necessary, even in asymptomatic women. 33% were concerned that something would be overlooked or missed if they did not receive a pelvic exam. Of the patients with an annual household income < $50, 000, 67% believed that the annual screening pelvic exam was necessary versus 100% with an annual household income > $50, 000 (p < 0.05). CONCLUSION: The majority of women disagreed with the recent USPSTF statement that the annual screening pelvic exam may be unnecessary.